Pemanfaatan Maksimum Sarana Dan Prasarana Sekolah Menengah Kejuruan (SMK) Karsa Mulya Dalam Rangka Meningkatkan Penerimaan Peserta Didik Baru - Kaenong, Hamiduddin Arief; Alexandri, Mohammad Benny; Sugandi, Yogi Suprayogi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
SMK Karsa Mulya is a private SMK in Palangka Raya that has the highest enrolment-to-learner ratio among other SMKs in the region, according to Dapodik data. In addition, this SMK also accommodates the largest number of learners, reflecting the excellent utilisation of facilities and infrastructure in supporting its enrolment capacity. Despite the limited facilities and infrastructure, SMK Karsa Mulya is still able to attract a large number of junior high school graduates. The learning strategy and cooperation with Iduka (Industry and the World of Work) that is implemented can be an example of good practice for other schools, regardless of the level of completeness of facilities and infrastructure owned. The purpose of the research is to find out the school management from both the Principal and the teachers so that junior high school graduates are still interested in entering SMK Karsa Mulya. The research method used is qualitative. To obtain information and data, interviews were conducted with the principal, teachers, and students of SMA Karsa Mulya. The results showed that the maximum utilisation of existing facilities and infrastructure, cooperation, communication, and maintaining trust with Iduka to utilise the equipment they have, good school management, the seriousness of the teachers to teach and provide good character education, the application of rules to create discipline, good handling of student conflicts, and good communication with students and parents are factors that make SMK Karsa Mulya continue to get students continuously and increase from year to year. This shows that the limited facilities and infrastructure owned by a school are not a significant barrier in getting a large number of students.